Effects of Cancer Treatment on the Nervous System, Volume 1. - Grisold, Wolfgang (Cambridge Scholars Publisher, 2020)
This first volume describes the epidemiology of cancer, development of drugs, chemotherapy and surgical therapy, and the side effects of therapies and differential diagnoses. It shows that the diagnosis of side effects needs to be supported by scales and scores to grade their extent, and presents a number of tools and methods that can be used to assess the focal and generalized effects of chemotherapy on the central and peripheral nervous system.Cancer is often associated with pain and is a frequent issue in patients with chemotherapy-induced neuropathy. The participation of patients in studie.